Composition and Abundance of Marine Debris and Microplastic in the West Coast Mangrove Ecosystem of Bintan Island - Anugrah, Septian; Syakti, Agung Dhamar; Suryanti, Ani (Department of Marine Science, Faculty of Fisheries and Marine Universitas Riau, 2024)
Plastic waste has been identified as an environmental problem by the UN Environment Program because it causes damage to the marine environment, organisms, and critical habitats. One ecosystem vulnerable to plastic waste is mangroves, so the government continues to tackle this problem. Bintan Island has a relatively large mangrove ecosystem, and some of it is included in the vulnerable category, so it is necessary to conduct a study regarding plastic waste and microplastics on Bintan Island. The research aims to identify the abundance of macro and meso debris in the mangrove ecosystem area, the abundance and characteristics of microplastics in sediment in the mangrove ecosystem area, microplastic contamination in gastropods (Telescopium sp), the relationship between mangrove density and macro debris density, and the relationship between macro debris density and mesoderm and microplastic. The research was conducted in October 2021 in Bintan Regency and Tanjung Pinang City. Data was collected using survey methods, microplastic abundance analysis, and correlation analysis. The mass of macro debris in the Tanjungpinang City administrative area is 743 g/m2. It is dominated by plastic, with a percentage of 49%, and meso debris, 94% of the total waste, is dominated by plastic waste. The characteristics of microplastics in sediment at each sampling location consist of fibers, fragments, and films. The most common microplastic contamination in Telescopium sp in the Bintan Regency area was film-type microplastics, totaling 198.33 particles. The relationship between mangrove density and macro debris generation is very strong, with a correlation value of 0.872. The relationship between the abundance of macro debris and meso debris and microplastics was strong, with correlation values of 0.972 and 0.793, respectively